2009
DOI: 10.1038/jhh.2009.98
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adiponectin concentration is associated with ambulatory daytime systolic blood pressure but not with the dipping status

Abstract: The objective of this study was to analyse the relationship between the ambulatory blood pressure (ABP) measurement and plasma adiponectin levels in a population-based cohort. Non-hypertensive, non-diabetics from the Oulu Project Elucidating Risk of Atherosclerosis cohort aged 40-60 years with ABP measurement available in 226 men and 236 women were analysed. ABP was recorded using the fully automatic SpaceLabs 90207 oscillometric unit. Plasma adiponectin concentrations were assayed using the enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(52 reference statements)
2
5
0
Order By: Relevance
“…The effects may be partially mediated by intra-hepatic fat accumulation, which also leads to decreased insulin sensitivity, or an adverse lipoprotein profile. 29,30 Like others, [31][32][33][34] we found an inverse relationship of adiponectin and systolic blood pressure. The mechanisms by which adiponectin can regulate blood pressure appear to be independent of body size, 31 and may be mediated through altered vascular reactivity.…”
Section: Discussionsupporting
confidence: 85%
“…The effects may be partially mediated by intra-hepatic fat accumulation, which also leads to decreased insulin sensitivity, or an adverse lipoprotein profile. 29,30 Like others, [31][32][33][34] we found an inverse relationship of adiponectin and systolic blood pressure. The mechanisms by which adiponectin can regulate blood pressure appear to be independent of body size, 31 and may be mediated through altered vascular reactivity.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have demonstrated that lower adiponectin levels are associated with a variety of cardiovascular risk factors including endothelial dysfunction, 7 increased carotid intima media thickness 8 and increased ambulatory blood pressure 9 (interestingly, as we observed for adiponectin genotype, the association with adiponectin levels appeared to be restricted to systolic pressure). Treatment of patients with type II diabetes with the PPAR-g agonist rosiglitazone results in a twofold increase in plasma adiponectin levels, 21 and specific adiponectin receptor agonists or adiponectin sensitizers have been suggested as potential treatments to reduce cardiometabolic risk.…”
Section: Discussionsupporting
confidence: 58%
“…[2][3][4] Adiponectin has been shown to suppress the transformation of macrophages into foam cells 5 and is detected in catheterinjured vessels but not in intact vessels. 6 Low adiponectin levels are associated with endothelial dysfunction, 7 increased carotid intima media thickness 8 and increased ambulatory systolic blood pressure (SBP) 9 whereas higher plasma levels have been associated with a lower risk of myocardial infarction. 3 A number of single-nucleotide polymorphisms (SNPs) in the ADIPOQ gene have been described.…”
Section: Introductionmentioning
confidence: 99%
“…51 Higher circulating adiponectin levels are associated with lower BP in humans. 5254 Metabolic syndrome and hypertension are associated with low adiponectin levels. 55,56 Importantly, subjects with low adiponectin levels exhibit cardiac sympathetic overactivity.…”
Section: Mechanisms By Which Obesity Increases Snamentioning
confidence: 99%